1998
DOI: 10.1063/1.121315
|View full text |Cite
|
Sign up to set email alerts
|

Field emission conduction mechanisms in chemical vapor deposited diamond and diamondlike carbon films

Abstract: Field emission properties of undoped chemical vapor deposited diamond and diamondlike carbon films have been measured for a variety of different deposition conditions. The nature and appearance of the damage site after testing, together with the mathematical form of the observed current-voltage relations, are correlated with the conductivity of the film. This is consistent with a model for the overall current which is a combination of conduction mechanisms through the bulk of the film with Fowler-Nordheim tunn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(33 citation statements)
references
References 6 publications
2
31
0
Order By: Relevance
“…Polymeric materials, with interesting electrical properties, have been studied in great details [1][2][3][4][5]. A good amount of work on the conduction mechanisms of PVC in the form of metal-polymer-metal (MPM) structure has been reported in the literature [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Polymeric materials, with interesting electrical properties, have been studied in great details [1][2][3][4][5]. A good amount of work on the conduction mechanisms of PVC in the form of metal-polymer-metal (MPM) structure has been reported in the literature [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…1, in the lower applied-bias region, the electrical data of these devices can be well fitted with Schottky emission equation [8][9][10], while, in the higher applied-bias region, the data can be well fitted with a power law, that is an indication of a space-charge-limited current (SCLC) mechanism [9][10][11]. This means that the conduction is mainly due to one carrier: the electron.…”
Section: El From Er-doped Sro Filmsmentioning
confidence: 99%
“…where e 0 is the dielectric constant of the free space and e r denotes the permittivity of the gate dielectric [10].…”
Section: El From Er-doped Sro Filmsmentioning
confidence: 99%
“…19,[29][30][31][32][33][34][35][36] The mechanism that a particular J(V) characteristic follows depends on the voltage range, the sample structure, and hence on the conditions and method of preparation. In the present work, we have found that the most suitable mechanism that can explain the behavior of the experimental data is the Richardson-Schottky (RS) mechanism.…”
Section: Electrical Measurements Theoretical Backgroundmentioning
confidence: 99%